State Fiscal Problems and Role of Central Assistance : The Case of North Eastern States of India - Dash, Ajit Kumar; Rath, Sudhansu Sekhar (Indian Journal of Finance, 2016)
This paper examined the fiscal problems and role of the central assistance in the context of fiscal management at the sub-national level, particularly with reference to special category states in India like the North Eastern states. Observing the status of fiscal autonomy, fiscal dependency, the mismatch between revenue receipts and expenditure, the study examined how the Central Plan Assistance, which has been received on the basis of gap filling approach has been used by these states for non plan revenue expenditure. The paper observed that there should be policy initiatives so that the North Eastern states are able to increase their own revenue and at the same time, the Central government should not only devolve resources ; rather, there should be a mechanism regarding how to control their non plan revenue expenditure so as to make the plan assistance available only for developmental expenditure.